A Review of Fatigue Performance Research on Aluminum Alloy Forming, Heat Treatment, Additive Manufacturing and Surface Modification Technologies - Baicheng Liu; Hongliang Zhang; Shenghan Li; Yurii Luhovskyi; Zhisheng Nong (Crystals, 2026)
Aluminum alloy is a lightweight, high-strength material based on aluminum matrix with the addition of elements such as copper, magnesium, silicon, zinc, manganese, or lithium. Featuring low density, high specific strength, excellent formability, and outstanding corrosion resistance, it is widely applied in the fields of aerospace, rail transit, automotive lightweighting, and additive manufacturing. In the aerospace sector, fatigue failure constitutes the primary failure mode of load-bearing components. This paper reviews the influence mechanisms of various strengthening technologies, namely shot peening (SP), laser shock processing (LSP), physical vapor deposition (PVD), micro-arc oxidation (MAO), anodic oxidation (ANO), additive manufacturing, casting, extrusion, and heat treatment, on the fatigue properties of aluminum alloys; analyzes the regulatory effects of process principles, coating compositions, and microstructures (grains, phase composition, and interfacial bonding) on crack initiation and propagation; discusses the synergistic effect between plastic deformation strengthening and coating functionality; summarizes the key material and process factors affecting the fatigue life of aluminum alloys; and finally prospects the technical development trends driven by high-reliability service requirements.